2011
DOI: 10.1111/j.1742-7843.2011.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antigenotoxicity of Baccharin, an Important Constituent of Baccharis dracunculifolia DC (Asteraceae)

Abstract: Baccharin (3-prenyl-4-(dihydrocinnamoyloxy)cinnamic acid) is an important chemical compound isolated from the aerial parts of Baccharis dracunculifolia DC (Asteraceae), a native plant of South America, and the most important plant source of Brazilian green propolis. The present study was designed to investigate the ability of baccharin to modulate the genotoxic effects induced by doxorubicin and methyl methanesulphonate in male Swiss mice using the micronucleus and comet assays, respectively. The different dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
9
0
3
Order By: Relevance
“…In addition, baccharin showed protective activity against methyl methanesulfonateinduced DNA damage in the comet assay (Oliveira et al, 2011). Analysis of the chemopreventive activity of baccharin by the micronucleus test showed that this prenylated phenylpropanoid could reduce the level of chromosome damage induced by doxorubicin.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, baccharin showed protective activity against methyl methanesulfonateinduced DNA damage in the comet assay (Oliveira et al, 2011). Analysis of the chemopreventive activity of baccharin by the micronucleus test showed that this prenylated phenylpropanoid could reduce the level of chromosome damage induced by doxorubicin.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that in about half of hospital admissions, physicians may make one prescribing error or the other. [7] Errors are more likely to occur with junior doctors[789] but are still prevalent in other senior categories of doctors. [710] Errors in prescribing can be attributed to a variety of factors including individual, environmental and organizational such as lack of knowledge, insufficient training, workload and communication.…”
Section: Introductionmentioning
confidence: 99%
“…Junior doctors are the most frequent prescribers in the hospital setting and are reported to make most of the prescribing errors. [7818] Knowing what drug to prescribe to which patient does not necessarily translate to a good prescription. Considering the fact that the majority of prescription-related errors in the hospital environment are made by junior doctors, it is necessary to educate the interns and develop interventions that will improve the prescribing qualities.…”
Section: Introductionmentioning
confidence: 99%
“…Other two compounds isolated from Rubus coreanus extract, and commonly present in other plant extracts of the genus Rubus also decreased the cytotoxicity of the chemotherapeutic agent cisplatin, in renal epithelial LLC-PK cells (Kim et al, 2011). Many other authors who studied compounds and extracts that exert antioxidant effects also demonstrated protection against reactive oxygen species generated by DXR administration (Ribeiro et al, 2010;Oliveira et al, 2011).…”
Section: Discussionmentioning
confidence: 95%